2022
DOI: 10.21883/eos.2022.06.54706.36-22
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of photoluminescence of carbon dots with different surface functionalization on hydrogen factor of water

Abstract: The pH dependences of the photoluminescence of carbon dots synthesized by the hydrothermal method with polyfunctional and monofunctional (carboxylated and hydroxylated) surfaces have been studied. As a result of the analysis of the obtained photoluminescence and absorption spectra of aqueous suspensions of all studied types of carbon dots at different pH values, a significant effect of the acidity of the environment of nanoparticles on their optical properties was found. It has been found that the greatest cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 24 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…It was previously shown that the main reason for the change of photoluminescence of CDs obtained by hydrothermal synthesis with the change of pH of the solution, , similar to other carbon nanoparticles–nanodiamonds, is (de)­protonation of surface groups. Deprotonation of surface groups occurs in the pH range from p K a – 1 to p K a + 1, where p K a is the decimal logarithm of the acid (or alkaline) K a index of certain surface groups.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…It was previously shown that the main reason for the change of photoluminescence of CDs obtained by hydrothermal synthesis with the change of pH of the solution, , similar to other carbon nanoparticles–nanodiamonds, is (de)­protonation of surface groups. Deprotonation of surface groups occurs in the pH range from p K a – 1 to p K a + 1, where p K a is the decimal logarithm of the acid (or alkaline) K a index of certain surface groups.…”
Section: Resultsmentioning
confidence: 95%
“…This means that small aggregation of nanoparticles occurs in water due to the interaction of richly developed surface groups of various nanoparticles with each other. It should be noted that three types of the main chemically active functional groups on the surface of CDs (carboxyl, hydroxyl and amide) at the specified measured pH value are in different states: carboxyl groups are deprotonated (−COO – ), hydroxyl groups are neutral (−OH), amide groups on sp 2 - and sp 3 -hybridized bases are excessively protonated (−NH 3 + ) and neutral (−NH 2 ), respectively , (for more details, see section ). It is most likely that the negative zeta potential of CDs is caused by the quantitative advantage of deprotonated carboxyl groups over positively charged groups.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation